Characterization and reuse of spent foundry sand in the production of concrete for interlocking pavement - Santos, L.F. dos [UNESP] (2021)
This paper presents the characterization of spent foundry sand mixtures (SFS-M) and a new use in the production of concrete blocks for interlocking pavement. Cylindrical and hexagonal concrete blocks were made with the total replacement of natural sand with SFS-M and their mechanical properties were evaluated. The fine aggregates were assessed by scanning electron microscopy, thermogravimetry, X-ray fluorescence and X-ray diffraction. The fresh and hardened concrete tests performed were slump, water absorption, void ratio and compressive strength. The compressive strength of samples with total replacement of natural sand with SFS-M was above 35 MPa. Water absorption was less than 6%, allowing its use as concrete pavement for light traffic. Thus, the results of this work indicated that the production of hexagonal concrete blocks with total replacement of natural sand with SFS-M is technically feasible and economically viable. The reuse of SFS reduces its disposal in landfills and also the use of natural resources resulting in less environmental impact.